SOSYAL BİLGİLER VE FEN BİLİMLERİ DERSLERİNİN ÖĞRETMEN YETİŞTİRME LİSANS PROGRAMLARI VE ÖĞRETİM PROGRAMLARI DÜZEYİNDE ÇEVRE KONULARI AÇISINDAN KARŞILAŞTIRILMASI - KARAKUŞ, Ufuk; KARAASLAN, Hüseyin; PEHLİVAN, Canan (Electronic Turkish Studies)
Environmental education is the subject of both applied and social science programs at secondary school level .This immediately brings the question how the common environmental issues are given using what themes in both disciplines. The prime target of this study is the determination of the courses related to the environmental issues in the teaching programs published by the Higher Education Council in 2007.these courses are then matched the gains indicated in the secondary education programs published in 2018 emphasizing the themes used in the environmental issues in the related courses. Finally the relations of these courses with the teacher education programs are compared and the relation between these programs in connection with the application of these courses at secondary education was determined. Also the connection between the applications of the environmental issues in both disciplines are explained .The data were analyzed by the qualitative analysis designed document investigation method. The data were evaluated by the use of deterministic approach. The study revealed that the applied sciences lecture gives the environmental topics by focusing the life within the integral entity of the environment while social sciences emphasize the human- environment relation and history of the environment. Also it was found that the topic of climate and food chain in science education program has no corresponding course in teacher education programs. It is obvious that there is an urgent need of examination of the common topics in social sciences programs with other disciplines in comparative manner.